The Effect of Brand Personality and Trust on Kiranti’s Brand Loyalty - Yessi Lusiana Dewi; Samsubar Saleh; Sampurno Sampurno (Faculty of Pharmacy, Universitas Gadjah Mada)
The marketing concept nowadays is more focused on creating long-term relationships with consumers who could give a positive impact on increasing market share and profitability. One of them can be achieved by establishing strong branding that influence customer loyalty. This study aimed to determine the effect of brand personality and trust on Kiranti’s brand loyalty. This research was an observational analytic study using cross sectional survey method. Data were obtained by questionnaire tools using 1-4 Likert scale. Sampling was conducted using non-probability purposive sampling. The samples were 100 people. The data were analyzed by simple and multiple linear regression analysis with a 95% of confidence level. The result showed that brand excitement and brand emotionality had positive and significant effect on brand trust, whereas the brand sophistication and brand activity had positive effect but notsignificant on brand trust. Brand excitement, sophistication brand, brand activity, and brand emotionality (or called brand personality)simultaneously had a positive and significant effect on brand trust with strong relationship. Brand trust had a positive and significant effect on Kiranti’s brand loyalty.Keywords: brand personality, brand trust, brand loyalty, Kiranti